Study on the Dynamic Response of Composite Box Girder Bridges with Corrugated Steel Webs - Ya-Na Mao; Chi Ma; Shi-Zhong Liu; Li-Yuan Li (Advances in Civil Engineering)
To more accurately consider the dynamic response of composite box girder bridges with corrugated steel webs under the effect of live loads, based on the theory of vehicle-bridge coupled vibration, a refined finite element model of vehicle-bridge coupled vibration analysis for composite box girders was established. The advanced dynamic response analysis of composite box girders with corrugated steel webs and traditional concrete box girders with 30 m single boxes and single cells, as well as with 50 m single boxes and multiple cells, was carried out. The research revealed that the natural vibration frequency of the composite box girder with corrugated steel webs is lower than that of the corresponding concrete box girder. When the bridge deck condition is poor, the dynamic impact coefficient of the composite box girder is much larger than that of the concrete box girder. When the bridge deck is in poor condition, the dynamic impact response is significantly enhanced, and the difference is significantly compared with that when the bridge deck is in good condition, which is greater than three times and even six times at the maximum. Both the difference in the vehicle model and the change in the vehicle speed influence the dynamic impact coefficient of the composite box girder.